The Effect of a Free Nutritious Meal Program on Elementary Students’ School Attendance Interest - Mugi Lestari; Muhammad Rizky Auliar; Nurfadhlina Abdul Halim (Research Collaboration Community (Rescollacom), 2026)
going to school remain significant challenges, particularly at the elementary level. One of the factors influencing students’ attendance is their level of interest, which can be affected by both internal and external conditions, including nutritional intake and economic background. The problem addressed in this study is whether the free nutritious meal program influences students’ interest in attending school. Therefore, this study aims to analyze the effect of a free nutritious meal program on students’ interest in attending school at SDN Nangoh. This research employs a quantitative approach using a survey method, with a total sample of 30 students from grades V and VI. Data were collected through a Likert-scale questionnaire and analyzed using Python, including validity testing (Pearson correlation), reliability testing (Cronbach’s Alpha), normality testing (Shapiro-Wilk), correlation analysis (Pearson and Spearman), and simple linear regression. The results show that all instrument items are valid and highly reliable, with Cronbach’s Alpha values of 0.935 (X) and 0.978 (Y). The normality test indicates that the data are not normally distributed, thus Spearman correlation is used, resulting in a very strong and significant relationship (ρ = 0.991; p < 0.05). Regression analysis reveals a significant positive effect (β = 1.053; p < 0.05) with a coefficient of determination (R²) of 0.990, indicating that 99% of the variation in students’ interest is explained by the program. In conclusion, the free nutritious meal program has a very strong and significant effect on increasing students’ interest in attending school, as it fulfills nutritional needs, enhances motivation, and reduces economic barriers.